2009
DOI: 10.1038/jes.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Urine-sampling methods for environmental chemicals in infants and young children

Abstract: This review paper examines and evaluates urine-sampling methodologies in infants and young children, to determine which methods are suitable for use in large biomonitoring surveys or studies of environmental chemicals in children younger than 6 years. Methods for non-toilet-trained children include the use of urine bags, collection pads (e.g., cotton or gauze inserts), disposable diapers, cotton diapers, and the clean catch method. In toilet-trained children, collection methods include use of a commode insert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 68 publications
(150 reference statements)
0
30
0
Order By: Relevance
“…In addition, among a small set of twin infants there was no correlation of urinary free or total BPA concentrations among the dyads. Given the concerns with the binding affinity and extraction recovery of the target biomarkers to the material used to collect the infant urine (Ye et al 2010), alternative collection approaches that do not require such an extraction (e.g., urine bags routinely used in hospitals) may be worth exploring (Lee and Arbuckle 2009). Although care was taken with the handling, transport and storage of the samples, it is still possible that contamination during collection or processing may have occurred or that some conjugated BPA may have reverted back to free BPA due to fluctuating temperatures (Ye et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, among a small set of twin infants there was no correlation of urinary free or total BPA concentrations among the dyads. Given the concerns with the binding affinity and extraction recovery of the target biomarkers to the material used to collect the infant urine (Ye et al 2010), alternative collection approaches that do not require such an extraction (e.g., urine bags routinely used in hospitals) may be worth exploring (Lee and Arbuckle 2009). Although care was taken with the handling, transport and storage of the samples, it is still possible that contamination during collection or processing may have occurred or that some conjugated BPA may have reverted back to free BPA due to fluctuating temperatures (Ye et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that collection and storage of biological specimens may affect biomonitoring results (Ye et al 2010; Lee and Arbuckle 2009; Calafat and Needham 2009) and field blanks were not collected in our study. Concentrations of free BPA in infant urine must be interpreted with caution because the urine was extracted from a woodpulp and cotton diaper (Ye et al 2010) and because we can’t rule out that contamination of the urine may have occurred (Völkel et al 2011).…”
Section: Limitationsmentioning
confidence: 95%
“…Many of the biomarkers evaluated eliminate in urine after exposure to ubiquitous environmental chemicals (e.g., phthalates, parabens, bisphenol A), but exposure to or contamination with these chemicals could also occur during urine collection, particularly because of the additional provisions necessary to collect the urine from young children compared to adults (Lee and Arbuckle, 2009). To minimize external contamination during the collection and processing of the urine, the protocol was designed to avoid materials known to contain the target analytes (e.g., wipe-containing parabens) and urine was collected only after the MEC staff instructed the child’s parent/guardian regarding the proper procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to blood and other matrices, collecting urine is generally considered a non-invasive and relatively easy procedure, at least for adults. However, collecting urine from young children who cannot easily void in regular urine collection containers can pose logistic challenges (Lee and Arbuckle, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation